Comparison of Computer-based Information Support to Clinical Research in Chinese and Japanese Hospitals - Jiang, G.; Ogasawara, K.; Endoh, A.; Sakurai, T. (Methods of Information in Medicine, 2002)
Objectives: The objectives of this research are to examine the current situation of computer-based information support of clinical research in hospitals and to determine the expectations of clinicians toward clinical research support functions of hospital information systems (HISs) in both China and Japan.Methods: 172 clinicians from 42 major hospitals in China (2 groups), and 568 clinicians from 79 university hospitals in Japan (2 groups), were surveyed by postal questionnaire during July and August, 1999. The Kruskal-Wallis test was performed to analyze the differences among the groups.Results: The total response rate was 66.9%. The result shows that 94.8% of the Japanese clinicians, 3.5 times more than those in China, use computers almost every day. High significance was shown for the frequency of non-HIS based information resources used by clinicians between China and Japan (p <0.001), whereas no significance for the frequency of HIS use by clinicians between the China I and Japan I groups (p = 0.725) was found. 33.3% clinicians in China thought they could obtain 30-50% of the necessary patient data for clinical research from the HIS, about 2 times more than in Japan (p = 0.009).Conclusions: Although the degree of computer involvement among clinicians in Japan is much higher than in China, the computer-based hospital information systems have not been developed well for supporting clinical research in both countries. The clinicians expect comprehensive computerized patient records (CPRs) and full use of patient related information in the existing HISs to support their clinical research.
Keywords: Hospital information systems; information storage and retrieval; clinical medicine; research; questionnaires